Phase transition and dielectric properties of PNNZT-BNLT ceramics - Butnoi P. (2014)
The (1-x)Pb(Ni0.33Nb0.67)0.5Ti0.3 5Zr0.15O3[PNNZT] - xBi0.4871Na0. 4871La0.0172TiO3[BNLT] ceramics (x = 0, 0.03, 0.06, 0.09, 0.12 and 0.15) were prepared by a two steps mixed-oxide method. XRD patterns of all ceramic samples exhibited a complete perovskite phase without pyroclore and no second phase. The BNLT addition has a significant effect on the grain growth inhibition of PNNZT-BNLT ceramics. The dielectric studies indicated that the phase transition behavior of the ceramic compositions becomes more diffuse with increasing BNLT content. The addition of BNLT content caused the increase in Tm, for example: about 16% for the 0.03 mol% BNLT sample while tanδ was reduced to about 60% compared with that of pure PNNZT sample. © 2013 Copyright Taylor and Francis Group, LLC.